Long‐term trends in critical care admissions in Wales*. (2nd May 2021) - Pugh, R. J.; Bailey, R.; Szakmany, T.; Al Sallakh, M.; Hollinghurst, J.; Akbari, A.; Griffiths, R.; Battle, C.; Thorpe, C.; Subbe, C. P.; Lyons, R. A.
Summary: As national populations age, demands on critical care services are expected to increase. In many healthcare settings, longitudinal trends indicate rising numbers and proportions of patients admitted to ICU who are older; elsewhere, including some parts of the UK, a decrease has raised concerns with regard to rationing according to age. Our aim was to investigate admission trends in Wales, where critical care capacity has not risen in the last decade. We used the Secure Anonymised Information Linkage Databank to identify and characterise critical care admissions in patients aged ≥ 18 years from 1 January 2008 to 31 December 2017. We categorised 85, 629 ICU admissions as youngest (18–64 years), older (65–79 years) and oldest (≥ 80 years). The oldest group accounted for 15% of admissions, the older age group 39% and the youngest group 46%. Relative to the national population, the incidence of admission rates per 10, 000 population in the oldest group decreased significantly over the study period from 91.5/10, 000 in 2008 to 77.5/10, 000 (a relative decrease of 15%), and among the older group from 89.2/10, 000 in 2008 to 75.3/10, 000 in 2017 (a relative decrease of 16%). We observed significant decreases in admissions with high comorbidity (modified Charlson comorbidity index); increases in the proportion of older patients admitted who were considered 'fit' rather than frail (electronic frailty index); and decreases in admissions with a medical diagnosis. In contrast to other healthcare settings, capacity constraints and surgical imperatives appear to have contributed to a relative exclusion of older patients presenting with acute medical illness.